2020
DOI: 10.48550/arxiv.2012.10517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning applications using diffusion tensor imaging of human brain: A PubMed literature review

Ashirbani Saha,
Pantea Fadaiefard,
Jessica E. Rabski
et al.

Abstract: We performed a PubMed search to find 148 papers published between January 2010 and December 2019 related to human brain, Diffusion Tensor Imaging (DTI), and Machine Learning (ML). The studies focused on healthy cohorts (n = 15), mental health disorders (n = 25), tumor (n = 19), trauma (n = 5), dementia (n = 24), developmental disorders (n = 5), movement disorders (n = 9), other neurological disorders (n = 27), miscellaneous non-neurological disorders, or without stating the disease of focus (n = 7), and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 166 publications
(309 reference statements)
0
4
0
Order By: Relevance
“…Previous studies used SVM and other ML statistical techniques with different DTI parameters and obtained variable levels of accuracy. [37][38][39][40][41][42][43][44]66,67 Vergara et al applied an SVM approach in mTBI patients, using FA and resting-state functional network connectivity (rsFNC) as features in their models. 38 They reported that rsFNC within the default mode network provided the best classification accuracy (84%), followed by FA (75.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies used SVM and other ML statistical techniques with different DTI parameters and obtained variable levels of accuracy. [37][38][39][40][41][42][43][44]66,67 Vergara et al applied an SVM approach in mTBI patients, using FA and resting-state functional network connectivity (rsFNC) as features in their models. 38 They reported that rsFNC within the default mode network provided the best classification accuracy (84%), followed by FA (75.5%).…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Saha et al recently reviewed 148 papers published between January 2010 and December 2019 related to the human brain, DTI, and ML, and identified five studies that involved the classification of TBI patients versus healthy controls. [37][38][39][40][41][42] Various DTI measures were extracted and used for voxel-based analysis, tractography, and generating connectivity matrices. Support vector machine (SVM) a supervised ML technique were used in all five studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a significant number of studies used machine learning methods for medical diagnosis [6,7]. The highest popularity among traditional machine learning has been gained by approaches that use support vector machines (SVM), support vector regression (SVR), and random forest (RF) classifiers [6].…”
mentioning
confidence: 99%
“…In the last decade, a significant number of studies used machine learning methods for medical diagnosis [6,7]. The highest popularity among traditional machine learning has been gained by approaches that use support vector machines (SVM), support vector regression (SVR), and random forest (RF) classifiers [6]. Advances in deep neural networks have opened a wide diagnostic opportunity in the classification and processing of medical imaging data offering additional benefits [7].…”
mentioning
confidence: 99%